103k views
2 votes
Given that f(x) = 2x + 5 and g(x) = x − 7, solve for f(g(x)) when x = −3. (1 point)

User Keithwill
by
6.5k points

2 Answers

5 votes
f(g(x))= 2(g(x))+5 = 2(x-7)+5 = 2x-14+5 = 2x-9
when x= -3
f(g(-3))= 2(-3)-9 = -6-9 = -15
User Samandmoore
by
6.4k points
3 votes

Answer:

-15

Explanation:

Given :
f(x) = 2x + 5


g(x) = x-7

To Find: solve for f(g(x)) when x = −3

Solution:


f(x) = 2x + 5


g(x) = x-7


f(g(x)) = 2(x-7)+ 5=2x-14+5=2x-9 ---1

Now we are supposed to find f(g(x)) when x = −3

So, substitute x = -3 in 1


f(g(-3)) =2(-3)-9


f(g(-3)) =-6-9


f(g(-3)) =-15

Hence f(g(x)) when x = −3 is -15.

User Paul Solt
by
6.0k points